2016
DOI: 10.1002/pc.24032
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Oil From Water Surface by Novel Composite NSM‐g‐P(MMA‐co‐BA) Super Oil‐Absorption Resin

Abstract: NSM‐g‐P(MMA‐co‐BA) resin with super oil‐absorbent capability was prepared by grafting co‐polymerization using Nitraria seeds meal as filler, methyl‐meth‐acrylate (MMA) and butyl‐acrylate (BA) as monomers, N,N′‐methylene‐bis‐acrylamide (MBA) as crosslinker and peroxide‐benzoyl (BPO) as initiator. The structure of obtained products was analyzed using Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM), respectively. The oil absorbency, reusability, oil‐retention capacity, thermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…The R 2 of the first-order sorption process showed a tiny gap with second-order sorption. Nonetheless, because of the limitation of the first-order sorption model, it was more suitable for describing the uncomplicated physical absorption or chemical absorption [ 41 ]. The sorption mechanism in the initial stage of PAMs was dominated by van der Waals forces and capillary dint, and the molecular diffusion dominated the sorption process [ 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…The R 2 of the first-order sorption process showed a tiny gap with second-order sorption. Nonetheless, because of the limitation of the first-order sorption model, it was more suitable for describing the uncomplicated physical absorption or chemical absorption [ 41 ]. The sorption mechanism in the initial stage of PAMs was dominated by van der Waals forces and capillary dint, and the molecular diffusion dominated the sorption process [ 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hai et al 127 reported a novel polymer composite resin material to treat oil spills. They attempted to synthesize a lipophilic composite resin by grafting copolymerization of methyl methacrylate and butyl acrylate on the surface of nitraria seeds meal (NSM), an important economic crop belonging to the zygophyllaceous (Figure 17A).…”
Section: Biopolymer Nanocomposite Sorbentsmentioning
confidence: 99%
“…(B) Oil absorbency of NSM‐ g ‐P(MMA‐ co ‐BA) resin in mixture of 0.9 wt% NaCl solutions and oil as a function of immersion time. (C) Removal of colza oil from 1 wt% NaCl solution using NSM‐ g ‐(PMMA‐co‐BA) Reprinted with copyright permission from Wiley online library 127 …”
Section: Biopolymer Nanocomposite Sorbentsmentioning
confidence: 99%
“…[3][4][5] Materials with special wettability have been developed based on bionic strategies and can separate oil/water mixtures via filtration. [6][7][8][9][10][11][12][13][14][15][16] In addition to immiscible oil/water mixtures, the separation of oil/water emulsions is also challenging, especially surfactantstabilized emulsions. [17][18][19] This is because the emulsion droplets with the action of surfactant exhibit high stability and complex structure, which makes it difficult to achieve effective aggregation of emulsion droplets.…”
Section: Introductionmentioning
confidence: 99%